Gerakan Beli Indonesia: Sebuah Kajian tentang Mentalitas Kaya di IIBF - Ibnu Kharis (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2017)
The condition of Indonesia that unchanged it’s because something that we build is merk, not build on the character. It’s very dangerous for Indonesia if Indonesia just build the merk and forget about the character building. For example, when going shopping are we think about that is Indonesian product or not? The Rich Nation mentality and Entrepreneurship is primer requirement for Indonesia at this time. Moreover develop of era and economic dynamical about free market impose we as Indonesia society to doing as player, not spectator. So unemployment problem and poverty can be solving. This paper will bring on the historical of Gerakan Beli Indonesia and about the mentality to be the rich nation mentality in Indonesian Islamic Business Forum (IIBF).